POSSIBILITIES OF SELF-ORGANIZATION METHODS IN PREDICTING EMERGENCY SITUATIONS IN MINING - I. S. Bondarenko; V. V. Kupriyanov (Вестник университета)
The article is directed at developing and substantiating one of the approaches to forecasting the individual residual resource of a particular mining equipment in operation in a coal mine clean-up area. The main causes, affecting the accuracy of forecasts, have been identified. The perspectivity of using complex forecasts on several analogs with the help of spline functions for variables, characterizing the technological situations with GGOs, has been shown. The procedure of short-term forecasting of the multidimensional process of changing the average annual values of variables describing technological situations with the conveyor and lava supports in the breakage face has been adduced. Successfully predictable and non-predictable variables have been revealed. Conducted complex forecasts for different criteria of self-organization have allowed us to set the optimal number of analogs and to rank the f